EFFECTIVES OF GRANULAR MATRIX SENSORS IN DIFFERENT IRRIGATION TREATMENTS AND INSTALLATION DEPTHS - Marković, Monika; Josipović, Marko; Šoštarić, Jasna; Zebec, Vladimir; Rapčan, Irena (Journal of Agricultural Sciences (Belgrade), 2016)
Continuous monitoring of soil moisture content plays a key role in irrigation scheduling and yield formation. This study was conducted to derive the technique and efficiency of application of granular matrix sensors (GMS) in a sprinkler-irrigation of maize (Zea mays L.). Two irrigation (a2 = 60%-100% field capacity (FC), a3 = 80%-100% FC) treatments were imposed during two growing seasons (2010, 2012) and compared with rainfed control plots (a1). GMS are used as an indirect method for monitoring soil water status on two depths (b1 = 15 cm and b2 = 30 cm) in order to make decision when to irrigate. The sensors used in this study were calibrated using a mass-based gravimetric method. In both growing seasons irrigation treatment and installation depths have significant influence (P<0.01) on soil water content. Sensors have shown satisfactorily response to wetting and drying periods in irrigation scheduling at 30 cm depth. Yet, doe to variability of weather conditions slow response to wetting and drying was in periods with intensive rainfall events (2010) and drought conditions with frequent irrigation intervals (2012).